Examining criticism of WHO’s COVID-19 response: a scoping review - Magde Mohamed Nour; Sezer Kisa; Adnan Kisa (Humanities & Social Sciences Communications)
Abstract The COVID-19 pandemic exposed significant weaknesses in global health governance, with the World Health Organization (WHO) facing widespread criticism. This scoping review aims to systematically examine and categorize critiques of WHO’s pandemic response across multiple stakeholders. Using Arksey and O’Malley’s framework and the Joanna Briggs Institute guidelines, a systematic search of six databases (CINAHL, Embase, Web of Science, Scopus, PsycINFO, and PubMed) was conducted. Peer-reviewed research studies were screened using predefined inclusion and exclusion criteria, and thematic synthesis categorized the findings across six key themes: delays in response, communication failures, vaccine equity, global coordination, governance limitations, and trust and transparency. Included studies reported that the WHO’s effectiveness was limited by delayed emergency declarations, inconsistent public health messaging, inequitable vaccine distribution, and constrained authority over global health measures. Additionally, geopolitical tensions, donor-driven funding structures, and the exclusion of key stakeholders (e.g., Taiwan) further challenged global coordination. These issues affected public trust and highlighted structural inefficiencies in international health governance. The findings point to calls for reforms, including enhanced autonomy in crisis response, more transparent communication strategies, equitable resource distribution, and strengthened mechanisms for global collaboration. This review contributes to the understanding of how health governance, public trust, and equity are interrelated, providing a foundation to inform efforts to enhance WHO’s leadership in future health crises.